EFFECT OF LAMBDA CYHALOTHRIN ON THE ACTIVITY OF GLYCOLYTIC PATHWAY AND MITOCHONDRIAL OXIDATIVE ENZYMES - Suman Gulati,; M. Priyadarssini,; E. Logeswari,; K. Revathi, (The Bioscan, 2025)
The application of pyrethroids as an insecticide and anti parasitary preparations has markedly increased. Fishes are extremely susceptible to these substances. An important factor is the rapid absorption of their accessibility, thus also the risk for aquatic organisms. The present study is a contribution to the assessment of toxicity and effects of lambda cyhalothrin on a benthic species, Clarias batrachus. Effect of lambda cyhalothrin on the activity of glycolytic pathway and mitochondrial oxidative enzymes were studied. Three groups of 25 fishes each were selected for the study. Specific activity of pyruvate kinase at different durations of exposure to the pyrethroid showed significant variation. Specific activity of citrate synthase after 45 days of exposure, the enzyme activity of the hepatic tissue of fishes of both experimental groups remained above the control levels. Specific activity of α-Ketoglutarate dehydrogenase in the various tissues viz., ovary, muscle, liver, heart and brain of the pyrethroid-exposed fishes showed a significant decrease (P<0.05) by the end of the exposure period of 45 days when compared to the control group. In fishes exposed to the higher sub-lethal concentration of lambda cyhalothrin, the ovary, muscle, liver, heart and brain tissues showed a significant decline (P<0.05) in the SDH enzyme activity at all durations of exposure to the pyrethroid in comparison to the control of animals. In the present study, the synthetic pyrethroid lambda cyhalothrin showed a significant inhibition of the malate dehydrogenase activity of the various tissues of Clarias batrachus even at sub-lethal concentrations. The liver tissue of pyrethroid-exposed fishes of both groups showed a gradual and significant decline (P<0.05) in the ATP levels throughout the exposure period when compared to the control group of fishes.